Studies on the interaction of mycobacterial products with phagocytes - Clara, Anna, Maria (My University, 1991)
This study assessed the effects of a 25kDa mycobacterial component on phagocyte functions associated with antimicrobial activity. (Abbreviation abstract)
Being a dissertation presented in fulfillment of the requirements governing the degree of Masters of Science in the School of Medicine, University of the Witwatersrand.
Keywords: Phagocytes.